Learning strategy adaptation of mainland Chinese international students studying humanities and social sciences subjects in French universities - Wu, Di; Cosnefroy, Laurent (Journal of further and higher education, 2025)
With higher education becoming highly internationalised, a large number of Mainland Chinese students pursue their studies abroad. While most research on Mainland Chinese students has been conducted in the context of English-speaking countries, research on students studying in France is scant. This study aims to investigate the influence of French higher education on Mainland Chinese students' learning strategies. Reflecting on a longitudinal approach, 30 students were interviewed twice at the end of their first semester and then at the end of their third semester at French universities. A thematic analysis of the interviews revealed four dimensions of difficulties that Mainland Chinese students encounter in French universities including less participation, group learning, teaching and learning, and assessment, which are the same as their compatriots studying in English-speaking universities. Faced with these difficulties, these students gradually adjusted their learning strategies, especially to the rote learning they are familiar with: they reduced rote learning and even added their understanding while learning by rote. They also adopted learning strategies that they rarely used in Mainland China including consulting external sources, seeking help from French lecturers or peers, and relating and structuring.